Analisis Model Faktor-faktor Penentu Kecenderungan Perilaku Kekerasan Siswa SMA - Syamsul Bachri Thalib (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2005)
This research was designed to explore the effects of extrinsic and intrinsic factors on violence. A structural equation model (SEM) was applied for analyzing more comprehensive and integrative determinant factors of violence, which involved 589 subjects (280 male and 309 female) of public school students in South Sulawesi. Extrinsic factors included violence experience, parenting, and parent education, while intrinsic factors included students’ temperament and self-concept. The research found that there was a positive correlation between violence’ experience with violence, and between authoritarian and permissive parenting with violence. There was a significant negative correlation between authoritative parenting with violence, between temperament with violence, and between self-concept and violence. There was significant difference of violence behavior between male and female student. The male student is higher than female student.